IMPLEMENTASI PEMBELAJARAN COOPERATIVE LEARNING DALAM MENINGKATKAN KERJASAMA ANTAR SISWA DALAM MATA PELAJARAN IPAS - Metha Pratiwi Erawan; Yesha Dwi Afrilia; Episiasi Episiasi (CV. ADIBA ASIHA AMIRA, 2025)
Cooperative learning is an approach aimed at enhancing cooperation among students in the teaching and learning process. This study aims to examine the effectiveness of implementing cooperative learning models in improving student collaboration in Science and Social Studies (IPAS) subjects. This research employs a qualitative approach with observation, interview, and documentation techniques to collect data related to students' responses and interactions during the learning process. The results show that the application of cooperative learning not only enhances students' understanding of the material but also strengthens their teamwork, sense of responsibility, and social skills within the group. Through cooperative learning, students are more active, supportive of one another, and highly motivated to grasp the subject matter. This indicates that the cooperative learning model has a significant contribution in supporting classroom learning success, especially in IPAS subjects.